Image denoising using bilateral filter with noise-adaptive parameter tuning - Gabiger-Rose, Anna; Kube, Matthias; Schmitt, Peter; Weigel, Robert; Rose, Richard (IECON 2011 - 37th Annual Conference on IEEE Industrial Electronics Society, 2011)
In this work, a novel way to adjust a bilateral filter is presented. The bilateral filter is a combination of domain and range filtering. The domain filter acts as a low-pass filter. The range filter stands for the nonlinear component and plays an important part in edge preserving. Both filtering components can be adjusted by according parameters. Pursuant to our experience and achieved results in terms of the image quality it is more effective to readjust the range filter to the noise level than to cope with the fine tuning of the spatial filter. In this work, we show how the adjustment parameter for the nonlinear range component can be derived from the standard deviation of noise, which allows automatic noise-adaptive adjustment of the filter.
elib2cris::1512001600,gabiger-rose2011b